Pag-IBIG Awareness and Financial Habits of Overseas Filipino Workers - Sorita, Irene; Zapanta, Tina Marie; Celis, Keziah Chim; Orfanel, Christine Joy; Manes, Luisito (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Many Filipinos prefer to work outside of the country because the opportunities and earnings are far superior to those offered in the Philippines. This correlational study aims to determine the awareness on Pag-IBIG Fund services and financial behavior and habits of Overseas Filipino Workers (OFW) members. The level of awareness of the Pag-IBIG Fund services includes Knowledge, Trust and Credibility, Sources and Channels, and Perceived Benefits, Barriers, and Engagement of OFW members while the efficiency level of financial behavior and habits of the members considers Savings Behavior, Investment Behavior, and Debt Management as factors. Furthermore, this study utilized a researchers-made survey questionnaire conducted to 300 respondents. Results revealed that OFW members are highly aware of the services offered by Pag-IBIG and they have high efficiency level when it comes to financial behavior and habits. Moreover, the correlation between years of employment and level of awareness on Pag-IBIG Fund services of the respondents as well as the efficiency level of financial behavior and habits and respondents’ demographic profiles are not significant. Further, the study exposed that OFW members exhibit a high level of efficiency in their financial behavior and habits, especially in savings and investment and a highly satisfactory awareness on Pag-IBIG Fund services. Specifically, age, gender, and civil status do not strongly influence financial efficiency while educational attainment impacts savings and debt management efficiency. Hence, these findings highlight the importance of education and awareness in fostering better financial habits among OFW members.